Preparation and Characterization of Wood Polymer Nanocomposites (WPNCs) for Sustainable Application - Md Tipu, Sultan (Universiti Malaysia Sarawak (UNIMAS), 2019)
ABSTRACT Wood impregnation is one of the oldest and the most frequently used techniques to improve the wood properties. This treatment offers a wide range of protection depending on used impregnates. Impregnation can make the wood more resistant to decay, less flammable, and can improve the mechanical property. Generally, the aim of this thesis is to improve the wood properties to already known technologies. To improve the wood properties, it is needed to simultaneously pluck out the lumen (by hydrophobic material) and the –OH group of raw wood, but the hydrophobic organic polymer cannot make a strong bond with wood. In this study, both the –OH groups, and lumens of wood were plucked out simultaneously by 4-methyl catachol or by a mixture of polymer/coupling agent/hydrophopbic nanoclay. In this study, 3-(trimethoxysilyl)propyl methacrylate (MSPMA), glycidyl methacrylate (GMA), maleic acid (MA), and ethylene glycol dimethacrylate (EGDMA) worked as a coupling agent between wood and polystyrene. One functional group of these coupling agents substituted the –OH group of wood and the other functional group having double bond formed a covalent bond with styrene by in situ polymerization. The effect of nanoclay on physical mechanical, thermal and biodegradation resistance properties of ST/coupling agent impregnated wood was studied. Two types of fungus, white-rot (Tramedes versicolor) and brown-rot (Coniophora putena), were used to study the biodegradability of impregnated wood. FT-IR result also proved that nanoclay helped to increase the interaction between wood and ST. The XRD result proved that nanoclay was exfoliated into wood. The SEM results showed that ST/coupling agent/nanoclay impregnated wood had smooth surfaces compared to ST/coupling agent impregnated wood and raw wood due to the exfoliation of clay into wood cell wall and polymer. With some exceptions, the MOR value, water uptake resistance and decay resistance of ST/coupling agent/clay impregnated wood were higher than that of ST/coupling agent impregnated wood. This is because hydrophobic nanoclay particles have high surface area, which increased the hydrophobicity in wood and also increased the compatibility between wood molecule and ST/coupling agent. The crystalinity breaking enthalpy of ST/coupling agent impregnated wood was higher than that of the ST/coupling agent impregnated/clay impregnated wood. So it can be expected that nanoclay increased the compatability between wood components and polystyrene. TGA results showed that the thermal stability (between 150-350 °C) of ST/coupling agent/clay impregnated wood were higher than that of ST/coupling agent impregnated wood. This higher stability of ST/coupling agent/clay impregnated wood can be explained that the wood and polymer were encapsulated by nanoclay. Finally it can be said that polymer/coupling agent/clay impregnated wood showed better wood properties than only polymer/coupling agent impregnated wood.